2021
DOI: 10.3390/ijms22052412
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Epigenetics in Asthma

Abstract: Asthma is one of the most common respiratory disease that affects both children and adults worldwide, with diverse phenotypes and underlying pathogenetic mechanisms poorly understood. As technology in genome sequencing progressed, scientific efforts were made to explain and predict asthma’s complexity and heterogeneity, and genome-wide association studies (GWAS) quickly became the preferred study method. Several gene markers and loci associated with asthma susceptibility, atopic and childhood-onset asthma were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 87 publications
0
77
0
13
Order By: Relevance
“…Genome‐wide sequencing and functional genes indicate that single nucleotide polymorphisms of GSDMB are related to the increased susceptibility of ulcerative colitis and Crohn's disease, as well as asthma exacerbations and antiviral pathways. 106 , 112 , 149 Analogous to GSDMA, GSDMB is also linked to childhood‐onset asthma, 154 while GSDMB (rs9303277) in CD4 + T cells is an SSc‐associated susceptibility locus. 115 In addition, GSDMB is included in the Type 1 and 2 diabetes (T1D, T2D) islet expression quantitative trait loci interaction network.…”
Section: The Mechanism Of the Pyroptosis Pathwaymentioning
confidence: 99%
“…Genome‐wide sequencing and functional genes indicate that single nucleotide polymorphisms of GSDMB are related to the increased susceptibility of ulcerative colitis and Crohn's disease, as well as asthma exacerbations and antiviral pathways. 106 , 112 , 149 Analogous to GSDMA, GSDMB is also linked to childhood‐onset asthma, 154 while GSDMB (rs9303277) in CD4 + T cells is an SSc‐associated susceptibility locus. 115 In addition, GSDMB is included in the Type 1 and 2 diabetes (T1D, T2D) islet expression quantitative trait loci interaction network.…”
Section: The Mechanism Of the Pyroptosis Pathwaymentioning
confidence: 99%
“…Other studies suggested that the many pathologies that characterized asthma might be explained by epigenetic imprinting of the developing lung during embryogenesis and early childhood [17,18]. The best studied epigenetic mechanisms related to asthma are histone modification, DNA methylation, and altered expression of specific micro RNAs (Figure 2).…”
Section: Early Events Leading To Asthma and Airway Wall Remodeling In...mentioning
confidence: 99%
“…Referring to some studies on the causes of airway wall remodeling during embryogenesis and early childhood [10][11][12], this hypothesis has been challenged [13][14][15][16][17]. The earlier assumption that asthma, atopy, and bronchial hyper-reactivity are caused by genetic modifications of immune regulatory proteins was not confirmed [13,18]. Nearly twenty years ago, the significantly increased thickness of the lamina reticularis due to increased collagen deposition correlated with the expression of the epidermal growth factor receptor, but without eosinophilic infiltration in children with asthma [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma is still one of the most common respiratory diseases [1,2], with 262 to 340 million cases worldwide, including 800,000 affected children living in Germany and a region-dependent incidence [3][4][5][6][7][8] associated with a high number of undiagnosed cases [9][10][11][12]. Based on the German national guidelines, the NVL Asthma 2020 (=Nationale Versorgungsleitlinie Asthma 2020), severe asthma exacerbation is defined by tachypnea, tachycardia, peak expiratory flow variations, reduced oxygen saturation, or speech dyspnea [13].…”
Section: Introductionmentioning
confidence: 99%